Percutaneous Coronary Sinus-Based Mitral Valve Repair Differentially Modulates Coronary Sinus to Mitral Valve Annulus Geometry and Topography - Rottländer, Dennis; Saal, Martin; Gödde, Miriel; Ögütcü, Alev; Degen, Hubertus; Haude, Michael (Frontiers in Cardiovascular Medicine, 2021)
Objectives: Coronary sinus (CS) based mitral annuloplasty using the Carillon device is a therapeutic option for the treatment of functional mitral valve regurgitation (FMR). Background: Little is known about the change of CS and MVA planes following Carillon implantation and how they are modulated by the tension applied on the device. Methods: In a retrospective single-center analysis 10 patients underwent Carillon device implantation and received CT-angiography prior and post CS based percutaneous mitral valve repair. Patients were assigned to responders or non-responders according to the 3-month transthoracic echocardiographic follow-up. A prototype software was used to assess distance and angulation of both CS (pre) or Carillon-device (post) and mitral annulus planes. Results: Comparison of the distance and angulation of the coronary sinus plane or Carillon device plane and the mitral valve annulus plane prior and post intervention showed a significant reduction of distance and unchanged angulation in responders while angulation was increased and distance reduced in non-responders without statistical significance. Furthermore, in FMR responders MVA perimeter, anterior-posterior diameter, intercommisural diameter and MVA area were decreased following successful indirect mitral valve annuloplasty, while in FMR non-responders Carillon device implantation had no effect on MVA geometry. Conclusions: Insufficient reduction of FMR following indirect mitral valve annuloplasty is associated with device malposition in relation to the mitral valve annulus. Patient selection using MSCT-derived distance and angulation of CS to MVA planes is one option to increase effectiveness of indirect mitral valve annuloplasty.